Montagem de Mosaico Com Imagens Aéreas para Auxílio a Equipes em Operações de Combate, Prevenção Ou Perícias em Incêndios Florestais Utilizando Drone - Amorim, Lúcio André (2016)
In this work we developed a system to collect, process and provide information extractedfrom aerial images captured by an aerial robot, known as UAV (Unmanned Aerial Vehicle).The focus is to assist a team of firefighters in operations of fire extinguishing, preventionor investigation. The project consisted on programming a ground processing station and acomputer onboard the aerial robot. The ground station is connected to the UAV througha telemetry link, and collects and stores GPS data supplied by a GPS unit onboard thevehicle. From the starting position and orientation of the UAV, as well as some parametersdefined by the operator (such as altitude of flight and area to be supervised), the groundstation defines a grid of 3D waypoints to be covered by the aerial robot during the flight.Such grid of waypoints is then delivered to the UAV. After that, the UAV goes to eachwaypoint, always sending its 3D position to its onboard computer, which controls thevehicle to reach every next planned point. When the aerial robot gets to a waypoint,the onboard computer keeps the vehicle hovering for a while in order to take a picturewith a camera attached to the UAV. All the images are stored in the memory of theonboard computer. Upon finishing the flight, the waypoint images and their correspondingGPS data are downloaded to the ground station, which processes the data using robustalgorithms. The result of such processing is a mosaic of the region over which the UAVflew, with the GPS coordinates of the waypoints included. The obtained mosaic is madeavailable for the operator. The steps involved in the development of the systems responsiblefor the communication between the ground station and the UAV, the image acquisition,the waypoint generation and mosaic building, including the algorithms adopted to buildthe mosaic, are all discribed in this dissertation. Finally, experiments are shown where theUAV flies over a region and the corresponding mosaic is generated, thus validating thefunctionality of the project.